Fighting Assessment Triggers Rapid Changes in Activity of the Brain Social Decision-Making Network of Cichlid Fish - Almeida, Olinda; Félix, Ana S.; Oliveira, Gonçalo A.; Lopes, João S.; Oliveira, Rui F. (Frontiers in Behavioral Neuroscience, 2019)
Social living animals have to adjust their behavior to rapid changes in the social environment. It has been hypothesized that the expression of social behavior is better explained by the activity pattern of a diffuse social decision-making network (SDMN) in the brain than by the activity of a single brain region. In this study, we tested the hypothesis that it is the assessment that individuals make of the outcome of the fights, rather than the expression of aggressive behavior per se, that triggers changes in the pattern of activation of the SDMN which are reflected in socially driven behavioral profiles (e.g. dominant vs. subordinate specific behaviors). For this purpose, we manipulated the perception of the outcome of an agonistic interaction in an African cichlid fish (Oreochromis mossambicus) and assessed if either the perception of outcome or fighting by itself was sufficient to trigger rapid changes in the activity of the SDMN. We have used the expression of immediate early genes (c-fos and egr-1) as a proxy to measure the neuronal activity in the brain. Fish fought their own image on a mirror for 15 minutes after which they were allocated to one of three conditions for the two last minutes of the trial: (1) they remained fighting the mirror image (no outcome treatment); (2) the mirror was lifted and a dominant male that had just won a fight was presented behind a transparent partition (perception of defeat treatment); (3) the mirror was lifted and a subordinate male that had just lost a fight was presented behind a transparent partition (perception of victory treatment). Results show that these short-term social interactions elicit distinct patterns in the SDMN and that the perception of the outcome was not a necessary condition to trigger a SDMN response in the perception of defeat treatment. We suggest that the mutual assessment of relative fighting behavior drives these acute changes in the state of the SDMN.